2009
DOI: 10.1007/s12032-009-9190-3
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α and its inhibitors in cancer

Abstract: Tumor necrosis factor (TNF)-alpha is implicated in the same time in apoptosis and in cell proliferation. TNF-alpha not only acts as pro-inflammatory cytokine conducing to wide spectrum of human diseases including inflammatory diseases, but can also induce tumor development. The molecular mechanisms of TNF-alpha functions have been intensively investigated. In this review we covered TNF-alpha, the molecule, its signaling pathway, and its therapeutic functions. We provide a particular insight in its paradoxical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 136 publications
(176 reference statements)
0
78
0
1
Order By: Relevance
“…30 Recent studies have also shown that DAPK1 is involved in a diverse range of signaling pathways and that it functions as a tumor suppressor. [31][32][33][34][35][36] However, whether and how DAPK1 is involved in virus-triggered type I IFN induction is unknown.…”
Section: Identification Of Dapk1 As An Irf7-interacting Proteinmentioning
confidence: 99%
“…30 Recent studies have also shown that DAPK1 is involved in a diverse range of signaling pathways and that it functions as a tumor suppressor. [31][32][33][34][35][36] However, whether and how DAPK1 is involved in virus-triggered type I IFN induction is unknown.…”
Section: Identification Of Dapk1 As An Irf7-interacting Proteinmentioning
confidence: 99%
“…The complex interactions between the neoplastic and inflammatory cells, which are mediated by inflammatory cytokines, are essential features of the tumor microenvironment [14] . Tumor necrosis factor-a (TNF-a) is a proinflammatory cytokine predominantly produced by macrophages as well as tumor cells [15,16] , and is a cytokine ligand of the TNF family that interacts with different receptors of the TNF receptor superfamily. The activity of this system may be one of the drivers of progression in CRC [17] .…”
Section: Introductionmentioning
confidence: 99%
“…It has multiple effects on cell function by binding to specific high-affinity, cell-surface receptors. Apart from its apoptosis-inducing mechanisms, TNF-a may promote tumor growth at lower levels during cancer progression [15,16] . A mounting body of evidence has suggested that TNF-a mediates many critical processes of tumor progression, including oncogene activation, DNA damage, and tumor metastases [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α does not only act as pro-inflammatory cytokine contributing to the wide spectrum of human diseases including inflammatory diseases, but can also induce tumor development. Therefore, the use of TNF-α inhibitors with a focus in cancer treatment has been taken into account [54]. With regard to our results of increased TNF-α expression by cancer cells and its role in other diseases we hypothesize the inflammatory mechanism of action by this cytokine as an example for the seventh 'hallmark of cancer' in CRC.…”
Section: Discussionmentioning
confidence: 72%
“…TNF-α is produced by macrophages as well as tumor cells and has multiple effects on cell function by binding to specific, high-affinity cell surface receptors. Beside apoptotic mechanisms, TNF-α may even promote tumor growth at lower levels during cancer progression [54,55]. Interestingly, during cancer progression tumor cells from CRC have been described to lose their susceptibility for the induction of apoptosis [5].…”
Section: Introductionmentioning
confidence: 99%